Present and Future of the Chilean Electrical Grid - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper presents a description of the current reality of the Chilean electricity sector and its future. The vision and its advancements in Chile are matter of observation to develop a clearer picture for maintaining and increasing the penetration of renewables towards global decarbonification and climate change mitigation. © 2019 IEEE.